Keefektifan Peer-Counseling (Konseling Teman Sebaya) Untuk Meningkatkan Resiliensi Remaja di Pondok Pesantren Bahrul Ulum Jombang - Muwakhidah, Muwakhidah (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
This research is based on phenomena that occur in the field that indicate attitudes and behaviors that lead to resilience or fighting power of pesantren adolescents. The purpose of this study was to increase the resilience of pesantren adolescents through peer counseling. The research design used a pretest-posttest control group design. There are two types of instruments used, namely treatment and measurement instruments. The treatment instrument consisted of a peer counseling guidebook, while the measurement instrument consisted of a resilience scale with a validity of 0.320 and a reliability of 0.855 and a student self-reflection sheet. Data analysis used the Two-Independent-Sample Test-Mann-Whitney U test. The results of statistical analysis showed that the calculated z value> z table is -3.315 and the Asymp value. Sig. (2-tailed) is 0.001 <0.05, then H0 is rejected. This means that peer counseling is effective in increasing the resilience of pesantren adolescents